Treatment Modality and Risk of Heart Failure in Patients With Long-Standing Graves’ Disease: A Nationwide Population-Based Cohort Study - Song, Eyun; Kim, Mina; Park, Sojeong; Park, Min Jeong; Kim, Jung A.; Roh, Eun; Yu, Ji Hee; Kim, Nam Hoon; Seo, Ji A.; Kim, Sin Gon; Kim, Nan Hee; Choi, Kyung Mook; et al. (Frontiers in Endocrinology, 2021)
Background: Optimal treatment for persistent Graves’ disease following 12–18 months of treatment with anti-thyroid drugs (ATDs) is unclear. Given the increased risk of cardiovascular morbidity and mortality with hyperthyroidism, assessing the risk of cardiovascular events associated with different treatment modalities after the conventional ATD course would be valuable in determining the appropriate next-line therapy. Methods: This retrospective cohort study included data from the Korean National Health Insurance database of 16,882 patients with newly diagnosed hyperthyroidism who received primary ATD treatment for 24 months. Patients were categorized based on the treatment they received after receiving ATD for 24 months: continued ATD for at least 12 more months (ATD group), radioiodine ablation (RIA) with remission (RIA group 1), and RIA without remission (RIA group 2). The incidence and risk of heart failure (HF), the leading cause of cardiovascular mortality in hyperthyroidism, were compared between patients and age-and sex-matched controls. Results: There were 16,516 (97.8%) patients in the ATD group, 230 (1.4%) in RIA group 1, and 136 (0.8%) in RIA group 2. Compared to that of controls, a significant difference in the cumulative incidence of HF was observed according to second-line treatment modality after adjusting for covariates; the risk was highest in patients in RIA group 2, with a hazard ratio (HR) of 2.54 (95% confidence interval (CI) 1.60–4.03), followed by those in the ATD group, with an HR of 1.23 (95% CI 1.20–1.36). Patients in RIA group 1 were not at an increased risk of HF compared to their matched controls (HR 0.77; 95% CI 0.38–1.54). When patients in the ATD group were further classified by the duration of ATD treatment at one-year intervals, the risk of HF was higher in patients with longer ATD use (p for linear trend < 0.001). Conclusions: In patients with long-standing hyperthyroidism treated with conventional duration of ATD therapy, the risk of HF was attenuated by RIA with remission of hyperthyroidism and increased as ATD was required for longer duration. To reduce the risk of HF, resolution of hyperthyroidism with RIA should be considered in patients with long-standing Graves’ disease.